Profile of family caregivers of elderly with ischemic cerebrovascular stroke - Chrytiany Plácido de Brito Vieira; Ana Virgínia de Melo Fialho (Rev Rene)
This study was accomplished with the aim of describing the socio-demographic and economical characteristics, of time in the function and support received by the family caregiver of elderly with ischemic cerebrovascular stroke. This is a descriptive and exploratory study with quantitative approach, carried out with elderly caregivers assisted at a reference neurology clinic in the city of Fortaleza-CE-Brazil, from May to August 2009. 52 family caregivers participated in the study, of which 32.8% were aged between 41 and 50 years; 92.3% female; 75% living with the elder; 63.5% were their son or daughter, followed by partners in 23.1% of the cases; 46.2% had only secondary education; 57.7% unemployed and had been caregivers for more than three years; 30.8% had income up to two minimum wages and 55.8% without any kind of support. These data reinforce even more the need of public policies to protect the elderly and also his caregiver.